2011
DOI: 10.1615/jlongtermeffmedimplants.v21.i4.20
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Dental Implants: Review of the Literature

Abstract: This study was conducted with the objective of examining and elaborating on the latest trends in the immediate loading of dental implants. It reviewed the materials and different techniques employed in immediate/early loading of implants in studies published since 2008. Articles were selected on the basis of a PubMed search that included controlled clinical studies of immediate loading of dental implants from the year 2008 onward. The inclusion criteria were a minimum of 10 patients in each group and a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In particular, the results of immediate loading in the maxilla have become more predictable and the selection criteria of patients and location for immediate loading have become more liberal. 5 It also seems that the addition of controlled loading does not compromise the outcome of immediate placement or of immediate loading. A systematic review of the current literature that comprised 34 prospective and retrospective studies, showed a survival rate >95%.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the results of immediate loading in the maxilla have become more predictable and the selection criteria of patients and location for immediate loading have become more liberal. 5 It also seems that the addition of controlled loading does not compromise the outcome of immediate placement or of immediate loading. A systematic review of the current literature that comprised 34 prospective and retrospective studies, showed a survival rate >95%.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many clinical studies proved that immediate restoration, immediate loading, or early loading are acceptable treatment modalities. [20,21] These studies were in response to the social and psychological needs of many patients. The immediate or early treatment modalities aim to reduce the overall recovery time between the surgical intervention and the insertion of the final restoration.…”
Section: Immediate and Delayed Restoration/loading What Is The Difference?mentioning
confidence: 99%